Investigation Potential of Ship Recycling Model: Literature Research - Muhammad Riyadi; Eda Turan (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2022)
Ship recycling pays attention globally as it becomes a need for sustainable development. Industrialized countries begin to move ship recycling activities to develop nations where labor is paid cheaply, and safety and environmental issues are not as strictly enforced. This challenge is mostly the effect of high costs as it occurs in a standardized process. This paper aims to identify a design of a cleaner production concept to improve the ship recycling model, where the negative impact caused by ship recycling needs to be minimized immediately through a sustainable approach. In order to convert ship dismantling into Green Ship Recycling, there are several ship recycling regulations that can be used as standardization and development that must be carried out based on guidelines related to technology and facilities, material handling, worker and environment safety, ship recycling plans, and the layout.